Understanding and challenging discourses of resilience in children's nursing to inform professional education - Clarke, Louise (2024)
Resilience is increasingly being advocated as a potential measure to reduce stress and burnout within the nursing profession. Consequently, nurse educators must integrate evidence-based resilience education into undergraduate nursing curricula. Within the UK, children’s nursing constitutes a distinct nursing speciality. Despite this there is a dearth of research into resilience within children’s nursing, and little is known about how children’s nurses conceptualise, experience, and nurture this attribute. A criticism of resilience research is that it lacks culturally sensitive definitions; and growing concern over the uncritical use of the term raises questions about normative concepts of resilience. This study contributes to a more sophisticated understanding of resilience within children’s nursing which has implications for nurse education, the profession, and future research. An interpretivist approach was adopted which employed certain research methods consistent with Heidegger’s principles of interpretative/ hermeneutic phenomenology. Purposive sampling techniques were utilised to identify two target groups of participants – qualified children’s nurses (QNs) and student nurses (SNs) studying to become children’s nurses. QNs in one healthcare trust, and year two and three undergraduate BSc SNs in one school of nursing were invited to take part in the study, resulting in ten QN and eight SN participants. Semi-structured interviews via Microsoft Teams were conducted and a social constructionist model of resilience was used as a lens to help interpret the findings. Descriptive coding was used in the first cycle of data analysis, followed by pattern coding. Finally, elements of theoretical coding were used to identify ‘umbrella’ themes central to the development of theory within this thesis. This study found that QN and SN participants defined resilience in terms of ‘coping’ and ‘carrying on’ in the face of chronic, endemic pressures as opposed to dominant definitions which position resilience as an ability to adapt to or bounce back from adverse events. Resilience was identified as a central element in the professional identity of a children’s nurse, and a strong desire to develop and demonstrate resilience was evident in both QN and SN participants. A significant pressure to demonstrate resilience was described; alongside a potentially maladaptive resilience discourse which encourages a culture where deficits in resilience are viewed as a personal weakness or failure. Such a discourse of resilience within nurse education and nursing practice, is problematic as it does not adequately account for the wider contextual challenges to resilience and may place unreasonable pressure on individuals to cope and make up for organisational deficits. There is a need to rethink such views to enable an understanding that everyone has capacity to be resilient but that there are varied ways to display it. This may enable a move away from unhelpful binary conceptualisations of resilience and help to counter the blame culture that is evident when nurses or students struggle to cope with ever increasing demands. Within this thesis, I propose that the phenomenon of resilience must be viewed within the context and demands of the profession. Furthermore, nurses and student nurses should be educated to understand that failure to cope with constantly increasing workplace demands does not constitute a failure of personal resilience and does not constitute a ‘weakness’ in themselves or others. Instead, increased focus should be placed on wider contextual stressors and QNs and SNs should be empowered to challenge unreasonable demands and request support to reduce endemic challenges to their resilience.